Os limites da solução mediada no direito de família - Sousa, Laura Zuppo de (2020)
The application of the practice of mediation may raise doubts among the participants as to what can be stated in a term of agreement. As a proper form of conflict treatment, it is notorious that mediation can be classified as a highly effective method when the intention is the definite resolution of the disputed issue. Based on this premise, the family was the object chosen to be submitted to mediation, and possible barriers to what can be determined by the parties involved in the family mediation session were examined. Both mediation as procedure and family as material object were studied in order to allow the conclusion reached. Despite the fact that the purpose of what may or may not limit the parties regarding the practical outcome of an agreement in family mediation has been explored in a descriptive and explanatory way, this was only achievable through the prior determination of the interaction between them. It concluded that the agreement in family mediation may assume characteristics of a sentence, when judicially approved, or of an agreement while it is only signed by the parties, being the unavailable rights and family principles the two factors that limit the autonomy of the parties in this procedure